Structure, Electronic, and Cv Properties of Hydroxy-Naphthaldehyde Schiff-Base Copper(Ii) Complexes Derived from Alkyl Amines: X-Ray Structure of Bis(N- I -Propyl-3-Hydroxy-2-Naphthaldiminato)Copper(Ii) - Zagal-Moya, J; Zagal-Moya, J; Costamagna-Martra, J; Costamagna-Martra, J (2012)
Copper(II) complexes with Schiff bases derived from linear and branched amines with 2-hydroxy-1-naphthaldehyde and 3-hydroxy-2-naphthaldehyde were synthesized and characterized by IR and electronic spectroscopies, magnetic susceptibilities, electrochemistry, cyclic voltammetry (CV), X-ray diffraction, and theoretical calculations. Electronic spectra are a function of the R group on the imine nitrogen of the ligand that determines steric effects. Complexes obtained from 3-hydroxy-2-naphthaldehyde ligand are more distorted from planarity in dimethylformamide solutions than those of 2-hydroxy-1- naphthaldehyde for the same R group. As a result, the former are easier to reduce to the related copper(I) complexes than those of 2-hydroxy-1- naphthaldiminate. The structure of bis(N-i-propyl-3-hydroxy-2-naphthaldiminato) copper(II) was determined by single-crystal X-ray diffraction. Its molecular structure can be described as distorted flat tetrahedral influenced by important packing effects and is flatter than that calculated with density functional theory methods. Additional related flat tetrahedral complexes were studied by theoretical calculations and it has been found that electronic effects also play a significant role. © 2012 Taylor and Francis.